Simple Imperative Model Programming Language for Education – SIMPLE - Rababaah, Aaron (2020)
This work presents the development of a new programming language, Simple Imperative-Model Programming Language for Education – SIMPLE. The new language is compiled procedural language that aims to simplify programming syntax and relives beginners from advanced programming concepts. SIMPLE was designed and implemented as a significant set of a typical procedural programming language. Although it is not intended for serious industry-level programming but, we claim that it could be an effective education vehicle and demonstrational component in introductory, intermediate and advanced courses. SIMPLE has been extensively tested using50+ different test programs designed carefully to target the language elements and features and our final tests showed that the language is reliable and ready to be adopted in education.